Minimum age of marriage under Islamic Law and the Islamic Family Law (Federal Territories) Act 1984: a preliminary study on the ideal age of marriage in Malaysia - Mohd, Azizah; A. Kadir, Nadhilah (International Institute of Islamic Thought and Civilization (ISTAC), 2019)
Marriage is a sacred institution the goal of which is to achieve mutual cooperation and happiness among the parties. As a religious covenant, marriage is to be contracted based on several essential requirements and conditions. Under Islamic law, the age factor is not listed as one of the requirements for a valid marriage. This is based on the fact that neither the Quran nor the Sunnah that indicates a specific age of marriage that may affect marriage validity. This has led to an assumption that there is no specific age of marriage under Islamic law. Nevertheless, the Muslim jurists are in agreement that a person is recommended to marry at an age where he or she understands the nature of the marriage contract, so that the marriage goals can be achieved. The issue arises as to what is the minimum age of marriage where a person is able to comprehend such marriage relationship. This paper seeks to primarily examine the issue of minimum age of marriage in Malaysia and the most suitable age of marriage under Islamic law that governs Muslims in Malaysia. The examination extends to juristic discourse on that matter and the incorporation of the Hanafi view and its significance on the minimum age of marriage that is recognized by the law in Malaysia. The research adopts a qualitative research methodology which primarily includes an examination of the primary and secondary sources relating to the subject matter. The research provides suggestions for the improvement of the law on minimum age of marriage in Malaysia where relevant and necessary.